HUBUNGAN ANTARA DIABETES MELITUS DENGAN GLAUKOMA - Layus Iranna Umayya; Indah Sapta Wardani (Jurnal Medika Hutama, 2023)
Diabetes Mellitus (DM) is a chronic disease caused by metabolic disorders with clinical signs of increased blood sugar levels that exceed normal limits. Management of DM must be done quickly, precisely, and continuously. If this is not done, it will cause various complications, one of which is glaucoma. Glaucoma is a chronic and progressive eye disease with damage to the optic disc and visual field defects caused by increased intraocular pressure due to obstruction of the eyeball's discharge (Aqueous Humor). There are several hypotheses which state that there is a significant relationship between DM and the incidence of glaucoma. If DM patients already have glaucoma complications, the treatment given must be a combination of DM and glaucoma management to produce a good prognosis.